Development of Video Games With WebGL Format That Allows You to Play Video Games Without Need for a Device With High Specifications - Dedi Prayudi; Nurul Hamdi (Brilliance: Research of Artificial Intelligence, 2023)
The rapid development of the gaming industry has brought new challenges in terms of hardware limitations faced by some players. Nowadays, many video games require devices with high specifications to provide an optimal gaming experience. However, this left several players with devices that were unable to run these video games. This research focuses on experimenting with video games in WebGL format that can run well on devices with low specifications, thereby allowing wider access to a quality gaming experience. In this research, the author tested video game performance on various devices with different specifications in WebGL format. The test results show that this approach succeeded in achieving the author's goal, namely that the video game still can be played on devices with low specifications.